Investigation of Titanium Dioxide Reinforcement on Thermal Performance of Siloxane Epoxy Based Intumescent Fire-Retardant Coating Systems - Suhardi, Muhammad Safiq Safwan Hady (Universiti Teknologi PETRONAS, 2017)
This report focusses mainly on the effectiveness of titanium dioxide reinforcement on thermal performance of siloxane epoxy based intumescent fire-retardant coating systems in providing passive fire proofing to steel substrates. Steel structures has the tendency to loss their load carrying abilities when the temperature of surrounding reach 500oC. This intumescent coating will help to shield the heat so that the steel structures do not collapse in case of fire emergency. In this project, mixtures consisting of melamine, boric acid, expandable graphite (EG), ammonium poly phosphate (APP) siloxane epoxy resin and ACR Hardener H-2310 polyamide amine were used to form the intumescent coating. A total of seven (7) formulations were developed to investigate the effects of Titanium Dioxide reinforcement on the intumescent coating. To study the formulation heat shielding and expansion of the char, furnace test was conducted. Fire test was carried out to analyses the temperature of coated steel substrate when directed to heat.